Analisis Keselamatan Pekerjaan Untuk Penilaian Dan Pengendalian Risiko Kecelakaan Kerja Di Bagian Produksi PT Wijaya Karya Beton Tbk PPB Majalengka - Parwati, Erni Widia, Tarwaka, PGDip Sc, M.Erg, Dr. Suwaji, M.Kes (2015)
Job safety analysis or job safety analysis is a technique for identifying and analyzing hazards in a job so that any type of work can be done the proper and effective prevention. The purpose of this study was to analyze the safety of activity as a risk assessment and control of occupational accidents in PT Wijaya Karya Beton Tbk PPB Majalengka. This type of research is descriptive. Is the overall study population, amounting to 179 workers of the workshop division line 1 there are 10 people, production line 1 there are 80 people, line 2 workshops there are 9 people, production lines 2 there are 80 people. The research sample number 27 with Proportionate Stratified Random Sampling. Data analysis starting from determining the work to be analyzed, outlining the work into basic steps, identify potential hazards then carried out a risk assessment derived from the severity of the risks posed by hazards. Results of the analysis of the types of high-risk job of four divisions, namely cutting the iron, the process of spinning, bending iron and foundry, alternative controls implemented in the form of engineering, administrative, and personal protective equipment. Although the company has conducted a risk assessment and risk control there remains a work accident, this is because some labor does not obey the rules K3.